2011
DOI: 10.1021/bi2009773
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a Polar Molecule for Selective Cytoplasmic Delivery by a pH (Low) Insertion Peptide

Abstract: Drug molecules are typically hydrophobic and small in order to traverse membranes to reach cytoplasmic targets, but we have discovered that more polar molecules can be delivered across using water-soluble, moderately hydrophobic membrane peptides of the pHLIP® (pH Low Insertion Peptide) family. Delivery of polar cargo molecules could expand the chemical landscape for pharmacological agents that have useful activity but are too polar by normal drug criteria. The spontaneous insertion and folding of the pHLIP pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 26 publications
0
61
0
Order By: Relevance
“…This process has been used for the translocation and release of various payloads, including cell-impermeable model peptides, imaging agents and toxins into cancer cells. 1921 Importantly, pHLIP-mediated translocation of cargo molecules across the cell membrane is not mediated either by interactions with cell surface receptors or through formation of pores in cell membranes. Thus, pHLIP releases cargo molecules directly into the cytoplasm without the need to escape endosomes or lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been used for the translocation and release of various payloads, including cell-impermeable model peptides, imaging agents and toxins into cancer cells. 1921 Importantly, pHLIP-mediated translocation of cargo molecules across the cell membrane is not mediated either by interactions with cell surface receptors or through formation of pores in cell membranes. Thus, pHLIP releases cargo molecules directly into the cytoplasm without the need to escape endosomes or lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…While studying membrane protein folding, we discovered a peptide called pH (low) insertion peptide (pHLIP) that reversibly folds and inserts across membranes in response to pH changes, and this discovery has led to a unique way to target acidic tissue. Our biophysical studies have revealed the molecular mechanism of pHLIP action (1-3), and we have shown that pHLIP can target acidic tissue and selectively translocate polar, cell-impermeable molecules across cell membranes in response to low extracellular pH (1,(4)(5)(6)(7)(8)(9). pHLIP conjugated with fluorescent dyes, PET [ 64 Cu-DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) and 18 F], single photon emission computed tomography (SPECT; 99 Tc) probes, and gold nanoparticles targets acidic tumors (1,4,5,10,11).…”
mentioning
confidence: 99%
“…This coil inserts into cell membranes and thus allows selective targeting of cancerous tissue of low extracellular pH (pH 6.0-6.8) while avoiding retention in healthy tissue (pH 7.2-7.4). WT-pHLIP has been successfully tested in vitro as an agent for intracellular delivery of large polar cargo molecules (26)(27)(28)(29). In addition, WT-pHLIP promotes pHdependent fusion of pHLIP-coated liposomes containing gramicidin channels with cellular membranes, thus destroying the balance of monovalent ions (30).…”
mentioning
confidence: 99%